Invasive, aggressive mastoid bone eumycetoma: a treatment challenge. (3rd March 2021) - Yosif, Abubaker Ahmed; Bakhiet, Sahar Mubarak; Abdalla, Tagwa Hayder; Mhmoud, Najwa Adam; Siddig, Emmanuel Edwar; Fahal, Ahmed Hassan
Abstract: Mycetoma is a chronic granulomatous disease that significant affects the subcutaneous tissue and deep structures. Mycetoma is caused by certain fungi (eumycetoma) or higher bacteria (actinomycetoma). The clinical presentation is variable and depends on the causative agent. For proper treatment and patient management, an accurate diagnosis of the species is mandatory. The disease mainly involves the extremities and it is rarely seen in the head and neck or other sites. In this communication, we present an interesting case of both invasive and aggressive mastoid bone eumycetoma caused by Madurella mycetomatis . Such cases are defied by complex challenges in finding effective surgical and medical treatments when the patient does not respond to both prolonged and different antifungal therapies.